TOWARDS SUSTAINABLE RURAL ELDERLY CARE: AN OVERVIEW OF PENSION MODELS IN HEILONGJIANG PROVINCE, CHINA - Tahir, Putri Rozita; Tong, Liu (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
China’s rapidly aging population presents a major social and economic challenge, particularly in rural provinces such as Heilongjiang, where demographic decline and urban migration have weakened traditional family-based elderly care systems. This paper provides a comprehensive overview of the rural pension models available to elderly people in Heilongjiang namely, family-based care, institutional care, and community-based services and analyzes their structural characteristics, limitations, and interrelationships. Drawing on recent policy reports, national surveys, and academic literature, the study highlights that while family care remains culturally dominant, it is increasingly unsustainable due to the rise of “empty nest” households and declining rural incomes. Institutional care, though expanding, faces barriers of affordability, stigma, and uneven quality across rural areas. Meanwhile, community-based services are emerging as a promising yet underdeveloped model, constrained by weak infrastructure and limited government support. The paper proposes a diversified, complementary framework integrating all three models, emphasizing the role of policy coordination, fiscal support, and social innovation. It also identifies research gaps related to financing mechanisms, integration of health and long-term care, and digital inclusion for the elderly. The analysis is conceptually guided by the welfare pluralism perspective, which recognizes the interdependence of state, family, market, and community actors in elderly support. The study reveals that while family-based care remains culturally rooted, demographic and economic pressures require stronger institutional and community-based interventions. The paper concludes by proposing a complementary, integrated care framework to support policy development in rural aging management.